Comparative study on serum matrix metalloproteinases in various species of domestic animals - KRUPAKARAN, R PRAKASH; BALAMURUGAN, T C; LAKSHMI, R DURGA; SHEEBA, A; PERUMAL, P (The Indian Journal of Animal Sciences, 2016)
A study was conducted to evaluate the presence of matrix metalloproteinases (MMP) in the serum of domestic animal species. The serum samples were collected from four healthy male animals of each species, viz. goat, cattle, horse, rabbit, sheep, pig and 4 tumor affected dogs in a heparinzed vacutainer, during early morning before feeding the animals. All the serum samples were subjected to gelatin zymography. The major bands were observed at 220, 92 kDa of MMP-9 and 72 kDa of MMP-2 in all the species with minor variations in rabbit and goat. It was observed that these bands indicated the normal physiological state of the animals and in tumour samples, the intensity of both MMP-9 and MMP-2 was 2–3 times higher. The level of expression of latent form of MMP-9 band was comparable in goat, cattle, horse, sheep and pig and also they were as expressed in human, on contrast there was low level of expression in rabbit as it clearly indicated these MMP proteins were in low concentration in the serum of rabbit. The thickness of Pro-MMP-9 (92 kDa) band in horse serum was alike as in the human marker and it might be related to human protein. There was a faded band below 72 kDa band in all the species but it was absent in human serum as it could be the active form of MMP-2 (62 kDa). MMP-2 band in cattle and horse serum were correlated. The concentration of the MMP-2 band in sheep serum was higher than in the other species used in this study but it was lesser than the activity of protein isolated from canine tumor. It was concluded that MMP plays a significant role in normal physiological functions of every species and its activity was 4–5 times higher in tumor samples due to greater gelatinolytic activity. Thus, it was concluded that tumor samples exhibit greater gelatinolytic activity because of higher concentration of MMP proteins.